(untitled) (Indonesian Art and Justice Review, 2024)
Decolonization remains a critical issue in Indonesia, especially in the realm of cultural representation. This paper explores how Indonesian art can contribute to the decolonization process by challenging Eurocentric norms and reclaiming the representation of indigenous cultures. It investigates how indigenous artists and cultural practitioners are using contemporary art forms to assert their cultural identity, resist cultural appropriation, and reshape narratives that have historically marginalized indigenous perspectives. By focusing on the ways in which Indonesian art engages with colonial histories and global power dynamics, the paper argues that decolonizing art is an essential part of a broader social justice movement aimed at restoring cultural sovereignty to indigenous peoples.